Educational Behavior and Burnout Relationship among Physical Education Teachers: Hubungan antara Perilaku Pendidikan dan Kelelahan pada Guru Pendidikan Jasmani - Ghyaidh, Hussein Rashid (Indonesian Journal of Education Methods Development, 2025)
Background: Teacher burnout has become a growing concern, particularly in the field of physical education, where instructional and psychological demands are high. Specific Background: Educational behavior plays a crucial role in shaping teachers’ professional satisfaction and resilience. Knowledge Gap: However, limited research has explored how educational behavior relates to burnout, especially when examined through gender and years of service as moderating variables. Aims: This study aimed to determine the relationship between educational behavior and burnout among physical education teachers according to gender and years of service. Results: Findings revealed a significant inverse relationship between educational behavior and burnout, while gender and years of service showed no significant differences in educational behavior levels. Novelty: The study contributes new insights by contextualizing educational behavior as a psychological factor influencing teacher burnout in physical education. Implications: The results highlight the need for professional support programs that enhance positive educational behaviors and reduce burnout risk among teachers. Highlights:• The study identifies a negative correlation between educational behavior and burnout.• Gender and years of service showed no significant impact on educational behavior.• The research underscores the importance of professional development for teachers. Keywords:Educational Behavior, Burnout, Gender, Years of Service, Physical Education